PRAKTIK JUAL BELI FOTO DI KAWASAN WISATA RELIGI MAKAM GUS DUR TEBUIRENG JOMBANG PERSPEKTIF HUKUM BISNIS ISLAM - Azizah, Ninik (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2023)
This article discusses the practice of buying and selling photos in the religious tourism area of Gus Dur's tomb Tebuireng Jombang from a business law perspective. The practice of buying and selling photos in the religious tourism area of Gus Dur's Tomb, some consumers do not feel disadvantaged and some others feel disadvantaged by the presence of this amateur photographer. This is because people's culture now considers that photos can be used as a medium to capture events or daily activities and some consider this to be privacy. As a service provider, photographers should not use force if consumers are not interested in buying the photo. Meanwhile, from a legal point of view, if a consumer suffers a loss, it is estimated that the legal power of this business actor is still weak, because there is no legal umbrella for the official existence of this amateur photographer service. Islam provides space for consumers and producers to defend their rights in trade known as khiyar. The types of khiyar include Khiyar Majelis, Khiyar Syarat, Khiyar ‘Aib, Khiyar Tadlis and Khiyar Ru’yah